PARADOKS KEMAKMURAN: PERBANDINGAN SISTEM OTORITARISME NEGARA SINGAPURA DAN MYANMAR - Bella Saidah; Shezy Solevina; Elly Nurlia (Jurnal Ilmiah Hubungan Internasional Fajar, 2026)
Comparative political studies confront a fundamental paradox: the similarity of authoritarian systems between two countries does not guarantee identical economic outcomes. In Southeast Asia, Singapore (implementing an authoritarian system, lacking natural resources but prosperous) and Myanmar (implementing an authoritarian system, rich in natural resources but experiencing economic crisis) are two examples. This study aims to analyze the disparity in economic outcomes using Douglass North's institutional theory. This study employed a qualitative method with a case study approach, and data collection was conducted through literature review. The findings suggest that Myanmar implements a hard authoritarianism (extractive state) where informal institutions (military patronage and kleptocracy) cripple formal institutions, creating destructive incentives. Conversely, Singapore implements a soft authoritarianism (developmental state) where informal institutions (meritocracy and anti- corruption) strengthen pro-market formal institutions, encouraging productive investment. Thus, the primary determinant behind the extreme disparity in prosperity between these two countries is not the type of political regime but rather the quality and congruence of institutions. Keywords: Authoritarianism, Informal Institutions, Douglass North, Singapore, Myanmar